2021
DOI: 10.18775/ijmsba.1849-5664-5419.2014.74.1002
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Relationships between Authentic Leadership, Job Crafting, Psychological Capital and Organisational Innovation

Abstract: The financial business industry has a vital role in national economic development. In Thailand, financial businesses practice innovation to develop the organisation. Weighing on this matter, this study examined the impacts of authentic leadership, psychological capital, and job crafting on the organisational innovation of Thailand’s financial business sector. Survey questionnaires were distributed to 683 private company employees for example. Multiple linear regression analyses were employed as the data anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…As for the managerial implications, the current results suggest that the software development branch, as one of the most dynamic and important branches of the entire IT&C industry, should pay more attention to the transformational leadership practice because workers performance seems to be partially influenced (therefore positively influenced) by the managerial/leadership practices within an exclusively online world. The current suggestions gain even more importance because the IT&C industry is distinctive through its working methods and specific organizational behavior, where followers work remotely online as a rule [120,121]; teamwork brings into light peculiarities such as online-based task or progress communication, reaching even to online socialization because private language seems more adjusted to these singular individuals.…”
Section: Discussionmentioning
confidence: 99%
“…As for the managerial implications, the current results suggest that the software development branch, as one of the most dynamic and important branches of the entire IT&C industry, should pay more attention to the transformational leadership practice because workers performance seems to be partially influenced (therefore positively influenced) by the managerial/leadership practices within an exclusively online world. The current suggestions gain even more importance because the IT&C industry is distinctive through its working methods and specific organizational behavior, where followers work remotely online as a rule [120,121]; teamwork brings into light peculiarities such as online-based task or progress communication, reaching even to online socialization because private language seems more adjusted to these singular individuals.…”
Section: Discussionmentioning
confidence: 99%
“…He concludes by calling for improved leadership in PAM. Uppathampracha and Guoxin (2021) in their study found the relative importance of authentic leadership in enhancing organizational innovation. This seems appropriate for the actualization of ISO 55000, the first worldwide attempt to capture the generically applicable 'must do' items for the management of any asset type, worthy of serious study and application, as Ma et al (2014) clinch in their study.…”
Section: Authentic Leadership and Physical Asset Management Practicesmentioning
confidence: 93%
“…However, such problems usually trigger changes in selforganization and managerial methods, resulting in job restructuring and in the introduction of new models of work [51,52]. An increasing number of researchers stress the importance of job crafting in maintaining employee autonomy [31], motivation at work [53], individualization of work arrangements [9], and in creating conditions for innovation [54,55]. The literature offers proposals for changes that could encourage employees to adapt to their work in order to increase commitment and to achieve satisfaction [21].…”
Section: Methodsmentioning
confidence: 99%